2002
DOI: 10.1086/342658
|View full text |Cite
|
Sign up to set email alerts
|

The Zodiacal Emission Spectrum as Determined byCOBEand Its Implications

Abstract: We combine observations from the DIRBE and FIRAS instruments on the COBE satellite to derive an annually averaged spectrum of the zodiacal cloud in the 10-1000 lm wavelength region. The spectrum exhibits a break at $150 lm that indicates a sharp break in the dust size distribution at a radius of about 30 lm. The spectrum can be fitted with a single blackbody with a À2 emissivity law beyond 150 lm and a temperature of 240 K. We also used a more realistic characterization of the cloud to fit the spectrum, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 24 publications
(28 reference statements)
8
121
3
Order By: Relevance
“…They found that the bands keep high Q abs ∼ 1 up to λ ∼ 3 mm, implying that their constituent particles are macroscopic. The absorption efficiency of the smooth cloud decays in the microwaves, however, not exactly as sharply as the simple approximation of Fixsen & Dwek (2002) suggests. The inverse problem solution sometimes led Planck Collaboration XIV (2014) to negative absorption efficiencies of the smooth cloud or circumsolar dust ring and Earth-trailing blob.…”
Section: The Kelsall Modelmentioning
confidence: 77%
See 4 more Smart Citations
“…They found that the bands keep high Q abs ∼ 1 up to λ ∼ 3 mm, implying that their constituent particles are macroscopic. The absorption efficiency of the smooth cloud decays in the microwaves, however, not exactly as sharply as the simple approximation of Fixsen & Dwek (2002) suggests. The inverse problem solution sometimes led Planck Collaboration XIV (2014) to negative absorption efficiencies of the smooth cloud or circumsolar dust ring and Earth-trailing blob.…”
Section: The Kelsall Modelmentioning
confidence: 77%
“…Both the smooth cloud and the dust bands extend only up to the heliocentric distance of 5.2 AU, since Kelsall et al (1998) Kelsall et al (1998), gray area on the plot, and for the Planck HFI wavelengths by Planck Collaboration XIV (2014). Fixsen & Dwek (2002) have also used the data from the COBE FIRAS instrument to determine the annually averaged spectrum of the zodiacal cloud plotted here with a dotted line. the outer boundaries of the corresponding asteroid families.…”
Section: Cross-section Area Distributionsmentioning
confidence: 99%
See 3 more Smart Citations